Development of female parent sorghum with high lysine and threonine content in Mali - Maiga, A. M.; Diallo, A. G.; Daou, A. (Ms. Pranali K. Rangari, 2021)
Sorghum is poor in minerals, protein content and nutritional value for resource-poor farmers in Mali. It is therefore important to provide the population with high-yielding hybrids sorghum, more nutritious and adapted to the agro-ecological conditions of the country. From 2018 to 2020 seasons, activities were carried out at the research station of IER with a goal to identify maintainer lines containing high lysine and threonine content. However, twenty-six lines were maintainer of sterility with anthers color (white) and form (thin). Sixteen lines as partial maintainer of sterility or restorers of fertility. The color and form of anthers (BR lines) were plump and yellowish. Thirty-three lines were restorer of fertility (R lines). The color and form of anthers (R lines) were plump and yellowish. The nine B lines had a good grain qualities and endosperm textures. The grain weight was 101 to 375 g for all nine B lines. These nine B lines are worthy for developing sorghum hybrids containing high lysine and threonine content.
Journal of Genetics, Genomics & Plant Breeding 5(3) 63-71 (July, 2021)
Keywords: Maintainer; Restorer; Lysine; Threonine; Sorghum